2015
DOI: 10.1051/0004-6361/201425371
|View full text |Cite
|
Sign up to set email alerts
|

First detections of FS Canis Majoris stars in clusters

Abstract: Context. FS CMa stars are low-luminosity objects showing the B[e] phenomenon whose evolutionary state remains a puzzle. These stars are surrounded by compact disks of warm dust of unknown origin. Hitherto, membership of FS CMa stars to coeval populations has never been confirmed. Aims. The discovery of low-luminosity line emitters in the young massive clusters Mercer 20 and Mercer 70 prompts us to investigate the nature of such objects. We intend to confirm membership to coeval populations in order to characte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 126 publications
(132 reference statements)
2
20
0
Order By: Relevance
“…2 in Davies et al 2012) were identified as late WN Wolf-Rayet stars (see Fig. 3 in de la Fuente et al 2013). We concur with these results.…”
Section: Mass Denissupporting
confidence: 90%
See 1 more Smart Citation
“…2 in Davies et al 2012) were identified as late WN Wolf-Rayet stars (see Fig. 3 in de la Fuente et al 2013). We concur with these results.…”
Section: Mass Denissupporting
confidence: 90%
“…near-IR spectroscopy with ESO/ISAAC and the results of these observations are reported in Davies et al (2012) and de la Fuente et al (2013). The authors derived a 11 ± 2 kpc distance and showed that Mercer 81 was mainly populated with nitrogen-rich Wolf-Rayet and blue supergiant stars; in particular, sources 1278 and 1279 (labelled 8 and 2 in these papers, see Fig.…”
Section: Mass Denismentioning
confidence: 78%
“…The surface density of the W-R stars in the W-R region of NGC 5430 is more than 100 times higher than that of the Milky Way (Massey 2003;Mauerhan et al 2011;Davies et al 2012;de la Fuente et al 2013). Moreover, the HII region associated with the W-R region deviates from the global HII regions in terms of the luminosity function, which is similar to our Milky Way (Keel 1982).…”
Section: The Externally Triggered Starburst At the Bar Endsupporting
confidence: 67%
“…( (23) Chené et al (2013), (24) Rahman, Moon, & Matzner (2011), (25) Anderson et al (2011), (26) Marston et al (2013), (27) Kanarek et al (2014), (28) Davies et al (2012), (29) de La Fuente, Najarro, Davies, & Figer (2013), (30) Borissova et al (2012), (31) Mikles et al (2006), (32) Hyodo et al (2008), (33) Faherty et al (2014) (34) Smith et al (2012), (35) Corradi et al (2010), (36) Gvaramadze et al (2009), (37) Burgemeister et al (2013) He ii This paper has been typeset from a T E X/ L A T E X file prepared by the author.…”
mentioning
confidence: 99%